E-Marketing of Information Services in Yemeni Private University Libraries in Sana’a City - Al-Habbari, Samar Gamal (Arab Journal for Sciences and Research Publishing, 2023)
The present study aims to discover the reality of E-marketing of information services provided by the surveyed university libraries. The researcher uses the descriptive survey method, including a questionnaire as the main tool. It was applied to a sample of (26) private university libraries in Sana’a. The study findings show that the marketing in general obtains an overall average of (3.11 out of 5) with an (average) rating. At the level of fields, the service (product) came (3.57) with a (high) rating, secondly, electronic promotion (3.01), and thirdly, the beneficiaries, human resources (2.89), both with a (medium) and fourth rating; Electronic distribution with an average of (2.57) and an estimate (low), and finally electronic pricing (1.00) and an estimate (very low), The findings also show that (19) of the surveyed university libraries, representing 73.08%, do not have E-marketing for their available information services. On the other hand, (7) of these libraries, representing 26.92%, are electronically marketing their available information services. Based on the findings, the researcher recommended that the university libraries, which were surveyed and found that they do not have marketing, shall have to introduce the E-marketing process within their services, keep abreast of technological developments, and invest Web 2.0 Technologies in introducing and developing their marketing means and methods. In addition, the researcher put forward proposals for complementary future studies on the subject.